Ecological pressures and milk metabolic hormones of ethnic Tibetans living at different altitudes - Elizabeth A. Quinn; Geoff Childs (Taylor & Francis Group, 2017)
Background: Very little is known about how milk hormones, shown to influence growth during infancy, may contribute to patterns of altered growth in high altitude living infants. Aim: This study investigated the association between maternal BMI, the metabolic hormones adiponectin and leptin in human milk and infant weight for age z-scores (WAZ) in Tibetans. Subjects and methods: A sample of 116 mothers and infants (aged 0-36 months) were recruited from two locations: the Nubri Valley, Nepal (rural; altitude = 2400-3900 m) and Kathmandu, Nepal (urban, 1400 m). Milk samples, anthropometrics, biological data and environmental information were collected on mothers and infants. Milk was analysed for leptin and adiponectin. Results: Maternal BMI was significantly associated with milk leptin content, but not adiponectin in either group. In the rural high altitude sample, child WAZ declined with age, but no such decline was seen in the urban sample. Conclusions: Milk leptin and adiponectin were not associated with infant growth in the rural Nubri sample, but were both inversely associated with infant WAZ in the Kathmandu sample. It appears that, in ecologically stressful environments, associations between milk hormones and growth during infancy may not be detectable in cross-sectional studies.